Enhanced Liposuction New Perspectives and Techniques - Irvine Duncan, Diane (IntechOpen, 2022)
Liposuction began as a simple, minimally invasive method of reducing the amount of localized fat in a region. Today it is a sophisticated and complex process, with many variations in purpose and technique. In this book, a global slate of expert surgeons offers a detailed description of various minimally invasive and non-invasive options for contouring the face, neck, and body. Chapters detail the evolution and utilization of various energy-based devices and combination treatments. They also describe procedure limitations and treatment of complications. Finally, they discuss indications for various approaches with case study descriptions so readers might be assisted with treating patients in their everyday practice.